1991
DOI: 10.1111/j.1432-1033.1991.tb16466.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana H1 histones

Abstract: We have isolated two Arubidopsis thulium cDNA clones that encode different H1 histone proteins. The H1-3 and HI-2 proteins are 274 and 273 amino acids in length, respectively. Unlike the H1 histones within a single animal species, the two plant H1 proteins share little sequence similarity outside the protein's central globular domain. Within the globular domain, a pentapeptide that is extremely well conserved in animal Hl histones, is not found in either of the plant proteins. Southern blot analysis suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…In general, apicies and young tissues contain significant amounts of mRNA, but mature tissues do not. We found that the histone H1 mRNA is a polyadenylated message (data not shown) and, in this respect, it is similar to all the other reported higher plant H1 mRNAs [9,10,21,291. In contrast, the Volvox [20] and most animal cell histone H1 mRNAs are non-polyadenylated, and those which are generally fit into the category of developmental variants or replication-independent variants.…”
Section: Speciessupporting
confidence: 88%
“…In general, apicies and young tissues contain significant amounts of mRNA, but mature tissues do not. We found that the histone H1 mRNA is a polyadenylated message (data not shown) and, in this respect, it is similar to all the other reported higher plant H1 mRNAs [9,10,21,291. In contrast, the Volvox [20] and most animal cell histone H1 mRNAs are non-polyadenylated, and those which are generally fit into the category of developmental variants or replication-independent variants.…”
Section: Speciessupporting
confidence: 88%
“…None of the six bands was recognized by antibodies raised against the tobacco high-mobility group HMG1 protein (results not shown). The sizes of the two major bands (H1A and H1B) corresponded well to that of the typical major somatic plant H1 (equivalent to 250 to 280 amino acid residues; Gantt and Lenvik, 1991) and to the size predicted from the single histone H1 cDNA sequence that has been reported from tobacco, which encodes a protein of 282 amino acids (Szekeres et al, 1995). To determine whether this cDNA sequence codes for H1A or H1B, we used it as a template in an in vitro transcription/translation assay.…”
Section: Identification Of Linker Histone Variants In Tobaccomentioning
confidence: 84%
“…The hhoA mRNA is polyadenylated, as already indicated by the fact that several cDNA fragments have been cloned using anchor-dT as a primer for the ®rst strand synthesis. Poly(A)-containing transcripts have been described for histone genes from a number of organisms (Ehinger et al, 1990;Sanicola et al, 1990;Gannt and Lenvik, 1991;Ushinsky et al, 1997). The sequence of two independent cDNA clones shows a polyadenylation site at position 1528 (see Fig.…”
Section: Sequence and Transcription Analysismentioning
confidence: 96%